PENGGUNAAN BIOPESTISIDA UNTUK PENGENDALIAN HAMA TANAMAN - Abdullah Sarijan (AGRICOLA, 2011)
Pest attack in plant agriculture can damage plants or failed harvest. To handle damage in plant need to protect the plant from damage from the several way to handle the pest we can done.  The farmers on focus to use the pesticide several product in research showing the damage in happened in environment.  Because they use of pesticide, residue in chemistry product if we consume can get bad effect for the human being and animal.  If we compare with the other way the used other non chemistry pesticide is the best way to use by farmer.  Because the kinds of pesticide can be made by the farmer themselves, beside that the used of pesticide isn’t damage in environment.  The application technique is not different if the farmer used chemistry pesticide, that’s using the way of spreading.